Analisis Bibliometrik: Penggunaan Media Pembelajaran Macromedia Flash 8 di Sekolah Dasar (2019-2023) - Longso, Irmawati; Sukartiningsih, Wahyu; Istiq’faroh, Nurul (Green Publisher Indonesia, 2024)
Bibliometric research is very important to provide readers with an understanding of research trends, compare authors or journals, and measure research contributions in scientific literature with the keyword